Environmental & architectural phenomenology. Vol. 7, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 1996)
Vol. 7, No. 2, Spring 1996 (includes “items of interest,” "citations received,” book reviews of Walter & Mary Brennemans' Crossing the Circle at the Holy Wells of Ireland & Theodor Schwenk's Sensitive Chaos, and essays by Barbara Schaffer & Tom Jay).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals